2023
DOI: 10.1038/s42003-023-05198-y
|View full text |Cite
|
Sign up to set email alerts
|

The pharmacoepigenomic landscape of cancer cell lines reveals the epigenetic component of drug sensitivity

Alexander Joschua Ohnmacht,
Anantharamanan Rajamani,
Göksu Avar
et al.

Abstract: Aberrant DNA methylation accompanies genetic alterations during oncogenesis and tumour homeostasis and contributes to the transcriptional deregulation of key signalling pathways in cancer. Despite increasing efforts in DNA methylation profiling of cancer patients, there is still a lack of epigenetic biomarkers to predict treatment efficacy. To address this, we analyse 721 cancer cell lines across 22 cancer types treated with 453 anti-cancer compounds. We systematically detect the predictive component of DNA me… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…These together underscore the limitations of cell lines used in cancer therapy studies [15][16][17][18] , as their absence of comprehensive biological systems such as the immune system may constrain their capacity to accurately represent the efficacy of specific drugs in the human body. On the clinical side, epigenetic information (methylation) was identified more important for drug response prediction and the mechanism of drug response, which was also found to be highly related to drug sensitivity 46 and resistance 30,31 in cancer therapies. This highlights the need of incorporating methylation information for anti-cancer drug discovery and therapy design.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These together underscore the limitations of cell lines used in cancer therapy studies [15][16][17][18] , as their absence of comprehensive biological systems such as the immune system may constrain their capacity to accurately represent the efficacy of specific drugs in the human body. On the clinical side, epigenetic information (methylation) was identified more important for drug response prediction and the mechanism of drug response, which was also found to be highly related to drug sensitivity 46 and resistance 30,31 in cancer therapies. This highlights the need of incorporating methylation information for anti-cancer drug discovery and therapy design.…”
Section: Discussionmentioning
confidence: 99%
“…We have collected the copy number variations (CNV), and the mutation of 14,812 genes. For the methylation data, to be consistent with that of TCGA, we collected methylation measured by 450K array from 46 . Note that the original values in CNV are the normalized log2 ratios and we further converted these values to categorical copy number statuses following the same procedure 48 in TCGA.…”
Section: Genomics Of Drug Sensitivity In Cancer (Gdsc)mentioning
confidence: 99%
“…FZD10 expression, a WNT pathway receptor, is also correlated with survival outcomes, and its downregulation increases cisplatin sensitivity, as the authors demonstrated in functional studies using SKOV3 and OVCAR3 cell lines [73]. Despite the crucial role of cell lines in identifying potentially relevant methylation profiles and their molecular impact on tumour development and treatment response, results in these models may not translate to the solid tumour or the clinical phenotype [74][75][76].…”
Section: Methylation Patterns In Ctdnamentioning
confidence: 99%